Rysunki w średniowiecznych rękopisach – rekonesans - Leńczuk, Mariusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The aim of the article is to draw the readers’ attention to the decorative and illustrative elements present in almost all medieval manuscripts. Based on the example of three groups of codices: Opera medica, Opera varia, Sermones, the author analyses the drawings collected for a few dozens of manuscripts found in the Jagiellonian Library. Since contemporary subject literature does not include an appropriate scientific research that would characterise and classify such elements of medieval codices, the author describes them in the pragmatic context, especially in relation to the ways of organising the text and commenting on its content. The decorative and illustrative layer is yet to be comprehensively analysed, but the reconnaissance shows how vast in terms of quantity and how rich in forms it is.